Form of Legal Change of Establishment of a Limited Liability Company after the Ratification of the Job Creation Act to Realize Legal Certainty - Utari, Retno (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study focuses on discussing the form of legal change regarding the establishment of a Limited Liability Company (Company) after the ratification of the Job Creation Law where in the legal change there is a legal conflict. This study uses a normative juridical method with a statutory approach, a conceptual approach, and a comparative approach. After the ratification of the Employment Copyright Act, there are forms of legal changes to the establishment of the Company, including: Companies with UMK criteria can be established by one person and for their establishment there is no obligation to use a notarial deed. In addition, the organs and the amount of authorized capital of the Company have also changed. This change in provisions has resulted in legal uncertainty due to the phrase agreement in the definition of an individual company.